2013
DOI: 10.4172/2332-0702.1000118
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Efficacy of Different Teaching Methods of Tooth Brushing in Children Contributors

Abstract: Aim: The purpose of the study was to assess the effectiveness of three different 'methods of teaching' tooth brushing in young children and the effect of reinforcement on the learning skills of the child.Material and Methods: 60 children (7-9 years) were equally divided into 3 groups (Group I: Audio visual; Group II: individual instruction on cast; Group III-child as a model) based on the 'method of teaching' the tooth brushing to be used. Each group was further divided equally into reinforcer and non reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
3
11
1
3
Order By: Relevance
“…Vivek Rana et al assess the effectiveness of 3 methods of teaching tooth brushing in young children with mixed dentition: audio-visual aids, individual instructions to each child on cast and child as model along with the effect of reinforcement on the learning skills of the child (39). Their results, which are similar to ours, showed that the most effective method of oral hygiene instruction and reinforcement was individual instruction independent of the age of the child.…”
Section: S S U E 2 2 0 1 4 Medinform 57supporting
confidence: 79%
See 1 more Smart Citation
“…Vivek Rana et al assess the effectiveness of 3 methods of teaching tooth brushing in young children with mixed dentition: audio-visual aids, individual instructions to each child on cast and child as model along with the effect of reinforcement on the learning skills of the child (39). Their results, which are similar to ours, showed that the most effective method of oral hygiene instruction and reinforcement was individual instruction independent of the age of the child.…”
Section: S S U E 2 2 0 1 4 Medinform 57supporting
confidence: 79%
“…Assessment of the effectiveness of teaching methods of oral hygiene is being studied by different authors (39,40,41).…”
Section: S S U E 2 2 0 1 4 Medinform 57mentioning
confidence: 99%
“…Nearly similar methodology was followed by Srivastava et al They reported similar results where reinforcement of the brushing techniques again after few days resulted in better reduction of plaque scores in children. 2 Yet, in our study, it was found to be less effective. Although there was a significant difference in the plaque scores in the reinforcers and nonreinforcers, it did not influence the subjects in brushing better.…”
Section: Discussioncontrasting
confidence: 40%
“…2 In 1965, Loe and et al demonstrated that subjects with healthy gingiva developed clinical signs of gingivitis within two to three weeks of refraining from all oral hygiene practices due to undisturbed accumulation of dental plaque. On resumption of adequate oral hygiene, the gingival tissue inflammation subsided within a week.…”
Section: Introductionmentioning
confidence: 99%
“…Tooth brushing is the most used and efficient mechanical method to remove dental biofilm from all accessible tooth surfaces 2 . Published studies have shown that this method may cause tooth and composite abrasion.…”
Section: Introductionmentioning
confidence: 99%